MANIFESTO STORYTELLING: A NEW METHOD OF ORGANIZATIONS - Beris Artan Özoran (Akademik İncelemeler Dergisi)
In postmodern era, rational bound in consumption relations was untied. Signs, symbols and “meanings” created by organizations in consumption, have replaced the use-value of products. The “meanings” created by organizations through public relations, advertising and marketing affect the consumption decisions of individuals. Individuals buy the “meaning” attributed to the product together with the product. Storytelling emerges as an important tool for creating these meanings. Stories disseminate emotions and help to bound people. The purpose of the article is to discuss how "manifesto storytelling", a new way of storytelling, functions in the new conception of consumption. In this context, Dove’s “Real Beauty”, Diesel’s “Be Stupid”, Axe’s “Boys do Cry”, Nike’s “Find Your Greatness” campaigns were analyzed through multiple case study method by using descriptive analysis. It was concluded that “Manifesto storytelling” is used by organizations as a tool to create a sense of “being a part of a cause” and to establish an emotional bond with the consumer within the new conception of consumption.